Developmental insights into the pathology of and therapeutic strategies for DM1: Back to the basics. Issue 3 (13th January 2015) - Chau, Anthony; Kalsotra, Auinash; Trainor, Paul; Johnson, Randy
ABSTRACT Myotonic Dystrophy type 1 (DM1), the most prevalent adult onset muscular dystrophy, is a trinucleotide repeat expansion disease caused by CTG expansion in the 3′‐UTR of DMPK gene. This expansion results in the expression of toxic gain‐of‐function RNA that forms ribonuclear foci and disrupts normal activities of RNA‐binding proteins belonging to the MBNL and CELF families. Changes in alternative splicing, translation, localization, and mRNA stability due to sequestration of MBNL proteins and up‐regulation of CELF1 are key to DM1 pathology. However, recent discoveries indicate that pathogenic mechanisms of DM1 involves many other factors as well, including repeat associated translation, activation of PKC‐dependent signaling pathway, aberrant polyadenylation, and microRNA deregulation. Expression of the toxic repeat RNA culminates in the developmental remodeling of the transcriptome, which produces fetal isoforms of proteins that are unable to fulfill the physiological requirements of adult tissues. This review will describe advances in the understanding of DM1 pathogenesis as well as current therapeutic developments for DM1. Developmental Dynamics 244:377–390, 2015. © 2014 Wiley Periodicals, Inc.